(untitled) (Revista revoluciones, 2022)
This paper presents a social research that sought to deepen the historiographical debates situated in relation to politics, women and the history of San Juan. It was based on feminist theoretical lines and was able to develop a qualitative methodological strategy, which descriptively applied documentary observation as a data collection and processing instrument. It has identified a series of epistemological debates, whose combination and/or ordering, yielded the construction of a genealogy on some of the possible modalities of female political participation of San Juan women.